1998
DOI: 10.1111/j.1349-7006.1998.tb00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Other Risk Factors for Ovarian Cancer in a Case‐Control Study

Abstract: Because it has been suggested that an environmental factor may play a role in the etiology of ovarian cancer, a case-control study was conducted to assess some environmental and other risk factors for ovarian cancer from 1994 to 1996 in northern Kyushu, Japan. We analyzed the data of 89 cases with epithelial ovarian cancer and 323 controls without any cancer or ovarian disorder. After controlling for the effect of potential confounders, the odds ratios of ovarian cancer across increasing quartiles of the heavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 36 publications
(46 reference statements)
6
49
2
Order By: Relevance
“…In a case-control study on OC in Japan, the OR of OC across increasing quartiles of the heaviest body weight were 1.00, 1.15, 1.71, 2.29. 17) We found the OR for OC of women who showed the highest level of change in BMI (≥2.50) was 1.37 (Table IV). Our study suggested that substantial weight gain from 20 years old is a common risk factor for these three sites of cancers.…”
Section: Discussionmentioning
confidence: 95%
“…In a case-control study on OC in Japan, the OR of OC across increasing quartiles of the heaviest body weight were 1.00, 1.15, 1.71, 2.29. 17) We found the OR for OC of women who showed the highest level of change in BMI (≥2.50) was 1.37 (Table IV). Our study suggested that substantial weight gain from 20 years old is a common risk factor for these three sites of cancers.…”
Section: Discussionmentioning
confidence: 95%
“…Most case-control studies have reported no statistically significant associations between height and risk (9)(10)(11)(12)(14)(15)(16)(17)(18). Only one case-control study (22) observed a statistically significant elevated risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the association with ovarian cancer risk (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), but results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is uncertain whether epidemiologic findings obtained in Western countries may be generalized to the Japanese population. Few epidemiologic studies have been conducted in Japan (Inoue et al 1994;Hirose et al 1996;Mori et al 1998;Hirose et al 1999;Okamura et al 2006). Thus, risk factors of gynecologic cancers have not been fully clarified in Japanese population.…”
mentioning
confidence: 99%